THE EFFECT OF FINANCING ON PROFITABILITY OF ISLAMIC BANKS: AN ANALYSIS BEFORE AND DURING PANDEMIC - Saiq, Moh. Rif'an; Faisal, Yudi (Faculty of Economic and Business, University of Pasundan, 2024)
The study aims to examine the effect of sharia financing on the profitability of islamic banks. Sharia financing is measured from the financing most widely used by sharia banks, namely sales and purchase financing and profit sharing financing, while profitability is measured using ROA. This study uses a quantitative method with a comparative descriptive approach. The results of the study before Covid-19 showed that sales and purchase financing had a significant positive effect and profit sharing financing had a significant negative effect on profitability. While during Covid-19, the results of the study showed that sales and purchase financing had a positive but insignificant effect and profit sharing financing did not have a negative effect on profitability. This influence can be interpreted that the more the sales and purchase financing increases, the more profitability will increase, conversely, the more the profit sharing financing increases, the profitability of sharia banks will decrease.